A broadband SPR dual-channel sensor based on a PCF coated with sodium-silver for refractive index and temperature measurement - Zhiyong Yin; Xili Jing; Ge Bai; Chun Wang; Chaoyi Liu; Zhigang Gao; Kaifeng Li (Results in Physics, 2022)
When temperature and refractive index are measured in same spectrum, the measurement range of parameters is generally narrow due to bandwidth limitation. We proposed a sensor for simultaneous measurement of them in a wide wavelength range for this problem. The proposed sensor is a dual-channel structure based on the photonic crystal fiber (PCF) with three air holes and a polished plane. The silver film deposited on the polished plane is responsible for refractive index measurement, and the sodium film and polydimethylsiloxane (PDMS) filled in an air hole for temperature measurement. According to research findings, the two kinds of metal films work in different wavebands, which increases the sensing bandwidth and the measurement range of the parameters to be measured. Numerical results show that when the refractive index of analyte is 1.35 ∼ 1.41 and the temperature is 10 ∼ 60℃, the maximum spectral sensitivity of the sensor is 8400 nm/RIU and 10.2 nm/℃, respectively. The results show that the performance of the sensor is not sensitive to structural parameters. It makes the sensor easy to manufacture. The excellent performances and wide detection range make the proposed sensor have a good application prospect in biochemical detection, environmental monitoring, medical sensing, and other fields.